Assessing efficiency drivers in municipal solid waste collection services through a non-parametric method. (20th March 2017) - Guerrini, Andrea; Carvalho, Pedro; Romano, Giulia; Cunha Marques, Rui; Leardini, Chiara
Abstract: Municipal solid waste collection is a public service with impact on the environment, public health, and the appearance of a municipal area. The standard of efficiency achieved in providing this service has a direct impact on household expenditure, since the costs of collection are recovered through citizens' taxes. The failure to consider relevant performance drivers recently led some Italian waste utilities into bankruptcy and financial collapse. Following prior research to identify the environmental and operational variables affecting the efficiency and quality of waste collection services, this study applies a more suitable and robust non-parametric method based on conditional order-m efficiency to identify the performance drivers of the waste collection services in 40 municipalities in Verona province, Italy. The exogenous variables studied could be clustered as 1) customer features (size of population served, population density, tourist flows, and percentage of non-residential customers; 2) household features, measured by number of inhabitants per house; and 3) operational features, represented by tons of waste collected for each load, method adopted (curbside or street bin), and maturity achieved with a given method. The study demonstrates that all variables affect the cost efficiency of waste collection with different intensity and direction. Highlights: Integrating collection services of small municipalities does not improve the efficiency. Best practices should be adopted to collect waste of non-residential customers. Less famous resorts of the province should improve their collection activities. The curbside method should be implemented in all municipalities. Collection processes have to be innovated in highly populated areas.